The Evaluation of Patient Satisfction on The Quality of Medicine Prescribtion Service at the Government Owned Hospital of Karanganyar Regency - Saputri, Nikmah; Rejeki, Mirah (Urecol Journal. Part C: Health Sciences, 2023)
Pharmaceutical services are services directly and responsibily to patients related to the availability of pharmaceuticals that aim to improve patient quality patient satisfaction cannot be separated from the quality of health services, the better the service provided, the patient satisfaction will increase. To be able to see an increase in service quality, it can be identified by measuring the level of patient satisfaction survey. The purpose of this study was to determine the level of satisfaction of outpatients on the quality of drug prescription services at the hospital. This research was a descriptive quantitative study. The sampling technique uses probability sampling. Respondents in this study amounted to 181 respondents. The analysis used is unvariate analysis. The results showed that the level of patient satisfaction with pharmaceutical services seen from the tangible dimension was 50,3%, the reliability dimension was 53,0%, the responsiveness dimension was 54,7%, the assurance dimension was 56,9% and the emphaty dimension obtained a result of 53,6%. It can be concluded that from the results of the distribution table above, the largest percentage is the responsiveness dimension (64,7%) and the assurance dimension (56,9%).